Electronic-based patient-reported outcomes: willingness, needs, and barriers in adjuvant and metastatic breast cancer patients - Hartkopf, Andreas; Graf, Joachim; Simoes, Elisabeth; Keilmann, Lucia; Sickenberger, Nina; Gass, Paul; Wallwiener, Diethelm; Matthies, Lina; Ţăran, Florin-Andrei; Lux, Michael Patrick; Wallwiener, Stephanie; Belleville, Eric; et al. (JMIR cancer)
Background: Patient-reported outcomes (PROs) play an increasingly important role as an adjunct to clinical outcome parameters in measuring health-related quality of life (HRQoL). In fact, PROs are already the accepted gold standard for collecting data about patients’ subjective perception of their own state of health. Currently, paper-based surveys of PRO still predominate; however, knowledge regarding the feasibility of and barriers to electronic-based PRO (ePRO) acceptance remains limited.